The Challenge of Multiloculated Pediatric Hydrocephalus: a case report - Barbosa, Gabriele Sousa; Freitas Santana , Marília; Moreira Ferreira, Lara; Vasconcelos, Taíssa Ilário de; Aguiar, Samille Vitória Siqueira; Aspilicueta Pinto Filho , Washington; Barros Juca , Carlos Eduardo (Brazilian Journal of Case Reports, 2022)
Hydrocephalus is an unbalanced condition between the production and absorption of cerebrospinal fluid (CSF). We reported a child with multiloculated hydrocephalus who developed several complications. Our team was challenged to manage his issues during five years of follow up. We performed multicystic cerebral shunts despite the neuroendoscopic evidence.